2021
DOI: 10.3389/fvets.2021.653771
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Fermentation of High- or Low-Tannin Fava Bean on Glucose Tolerance, Body Weight, Cardiovascular Function, and Blood Parameters in Dogs After 7 Days of Feeding: Comparison With Commercial Diets With Normal vs. High Protein

Abstract: Fava bean, which is available in high- and low-tannin varieties, is not an approved pet food ingredient and was not included in the “assumed to be safe” category based on its ability to cause favism and hemolytic anemia in susceptible humans. The effects of 7-day feeding of test canine diets containing moderate protein (~27%) were compared with two control commercial diets with normal (NP, grain-containing, ~25% protein) or high protein (HP, grain-free, ~41% protein). Fava bean diets were formulated either wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
13
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(30 citation statements)
references
References 58 publications
(72 reference statements)
8
13
4
Order By: Relevance
“…We are unable to make inferences about bioavailability in the present study; however, fermentation was observed to increase protein digestibility in low tannin compared to high tannin fava bean varieties and increased gross energy digestibility in low tannin only. These findings contrast with our short-term study where there was no effect of fava bean variety on digestibility values of any nutrient measured [19]. This indicates that the negative effects of anti-nutritional factors may be directly associated with feeding period length.…”
Section: Toxicity From Fava Beans Digestibility Glucose Tolerance And...contrasting
confidence: 99%
See 4 more Smart Citations
“…We are unable to make inferences about bioavailability in the present study; however, fermentation was observed to increase protein digestibility in low tannin compared to high tannin fava bean varieties and increased gross energy digestibility in low tannin only. These findings contrast with our short-term study where there was no effect of fava bean variety on digestibility values of any nutrient measured [19]. This indicates that the negative effects of anti-nutritional factors may be directly associated with feeding period length.…”
Section: Toxicity From Fava Beans Digestibility Glucose Tolerance And...contrasting
confidence: 99%
“…In the present study, fermentation decreased the vicine and convicine content in fava bean flours and did not influence plasma taurine content or amino acid digestibility after 28-day feeding, which is in agreement with our previous findings in a short-term feeding period [19]. It has been recently shown that fermentation with L. plantarum effectively degraded the pyrimidine glycosides in fava bean flour within 48 h, which attenuated the toxicity of the fermented diets [22].…”
Section: Toxicity From Fava Beans Digestibility Glucose Tolerance And...supporting
confidence: 93%
See 3 more Smart Citations